2002
DOI: 10.1165/ajrcmb.27.2.4703
|View full text |Cite
|
Sign up to set email alerts
|

Defective Pulmonary Development in the Absence of Heparin-Binding Vascular Endothelial Growth Factor Isoforms

Abstract: Development of the airways, alveoli, and the pulmonary vasculature in the fetus is a process that is precisely controlled. One of the growth factors involved, vascular endothelial growth factor (VEGF), is so critical for embryonic development that in the mouse, elimination of just a single allele is lethal. In the early stages of lung development, the mouse VEGF gene expresses three isoforms (120, 164, and 188) in a distinct temporo-spatial pattern, suggesting a specific function for each. We engineered mice t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
107
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 148 publications
(111 citation statements)
references
References 26 publications
3
107
1
Order By: Relevance
“…Our study demonstrated that PTX treatment during hyperoxia is able to markedly increase pulmonary vascular density, which may be induced by increased VEGF expression. We found that VEGF121 expression was constant in all three study groups, indicating that VEGF121 may not be influenced by oxygen stress as seen in a rabbit model (28). Previous studies have shown that VEGF121 is a predominant form before embryonic day 14, indicating that this isoform has a unique role early in lung development (29), with perhaps a less important role toward birth, leading to a decreased expression and a lack of response during oxygen exposure.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…Our study demonstrated that PTX treatment during hyperoxia is able to markedly increase pulmonary vascular density, which may be induced by increased VEGF expression. We found that VEGF121 expression was constant in all three study groups, indicating that VEGF121 may not be influenced by oxygen stress as seen in a rabbit model (28). Previous studies have shown that VEGF121 is a predominant form before embryonic day 14, indicating that this isoform has a unique role early in lung development (29), with perhaps a less important role toward birth, leading to a decreased expression and a lack of response during oxygen exposure.…”
Section: Discussionsupporting
confidence: 55%
“…Different isoforms have different affinities for heparin and receptors, and distinct tempo-spatial expression of these isoforms suggests different function. Mice expressing only VEGF121 had impaired lung vascular and airspace formation, indicating an essential role for the heparin sulfate-binding VEGF165 and VEGF189 isoforms in lung development (28). In our study, we demonstrated that PTX protects against hyperoxia-induced (13).…”
Section: Discussionsupporting
confidence: 51%
“…Several studies support the notion that ECs within the lungs actively promote normal alveolar growth and lung regeneration (15). Conversely, genetic or pharmacological antagonism of the VEGF nitric oxide pathway can lead to decreased lung angiogenesis and poor lung regeneration (41). Similar to the liver and lung regeneration discussed above, kidney blood vessels appear to have a role in kidney regeneration (42).…”
Section: Discussionmentioning
confidence: 92%
“…Microvascular development, which is essential for efficient gas exchange, is regulated by vascular endothelial growth factor (VEGF), which has been shown to be disrupted in BPD (12)(13)(14). Exposure to high concentrations of oxygen during lung development results in lung injury characterized by alterations in capillary density, endothelial cell destruction, pulmonary inflammation, and inhibition of the process of alveolarization (15)(16)(17)(18)(19).…”
mentioning
confidence: 99%
“…VEGF is a potent, endothelial cell mitogen that stimulates vessel proliferation, migration, and tube formation leading to angiogenic growth of new blood vessels (15)(16)(17)(18)(19). It is essential for angiogenesis during development; the deletion of a single allele arrests angiogenesis and causes embryonic lethality (20)(21)(22).…”
mentioning
confidence: 99%